Malnutrition / Margaret Haerens - Haerens, Margaret
From Booklist: "Each volume in the Opposing Viewpoints Series could serve as a model-not only providing access to a wide diversity of opinions, but also stimulating readers to do further research for group discussion and individual interest. Both shrill and moderate, the selections-by experts, policy makers, and concerned citizens-include complete articles and speeches, long book excerpts, and occasional cartoons and boxed quotations-all up to date and fully documented. The editing is intelligent and unobtrusive, organizing the material around substantive issues within the general debate. Brief introductions to each section and to each reading focus the questions raised and offer no slick answers."